Attention, Gestalt Principles, and the Determinacy of Perceptual Content - White, Benjamin (My University, 2020)
Theories of phenomenal intentionality have been claimed to resolve certain worries about the indeterminacy of mental content that rival, externalist theories face. Thus far, however, such claims have been largely programmatic. This paper aims to improve on prior arguments in favor of phenomenal intentionality by using attention and Gestalt principles as specific examples of factors that influence the phenomenal character of perceptual experience in ways that thereby help determine perceptual content. Some reasons are then offered for rejecting an alternative interpretation of these examples, according to which the phenomenal effects of attention and Gestalt principles play no role in the determination of perceptual content.
IN_PRESS
Keywords: Phenomenal intentionality; Perceptual content; Content indeterminacy; Attention; Gestalt principles; perceptual content